2018
DOI: 10.1186/s10020-018-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

AEG-1 is involved in hypoxia-induced autophagy and decreases chemosensitivity in T-cell lymphoma

Abstract: BackgroundThis study was to examine the link between astrocyte elevated gene-1 (AEG-1) and hypoxia induced-chemoresistance in T-cell non-Hodgkin’s lymphoma (T-NHL), as well as the underlying molecular mechanisms.MethodsExpression of AEG-1, LC3-II, and Beclin-1 were initially examined in human T-NHL tissues (n = 30) and normal lymph node tissues (n = 16) using western blot, real-time PCR and immunohistochemistry. Western blot was also performed to analyze the expression of AEG-1, LC3-II, and Beclin-1 in T-NHL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…MTdH has been reported to be associated with autophagy. The overexpression of MTdH induces autophagy, while downregulation of MTdH suppresses autophagy (38,39). However, it has also been found that the simultaneous inhibition of autophagy and overexpression of MTdH decreases the levels of P-gp and inhibits 5-Fu resistance (40).…”
Section: Mir-22 Inhibits the Proliferation Of Mg-63 Cells And Mg-63/cmentioning
confidence: 99%
“…MTdH has been reported to be associated with autophagy. The overexpression of MTdH induces autophagy, while downregulation of MTdH suppresses autophagy (38,39). However, it has also been found that the simultaneous inhibition of autophagy and overexpression of MTdH decreases the levels of P-gp and inhibits 5-Fu resistance (40).…”
Section: Mir-22 Inhibits the Proliferation Of Mg-63 Cells And Mg-63/cmentioning
confidence: 99%
“…In T-cell lymphoma, autophagy was shown to be increased when cells were incubated in hypoxic conditions. Hypoxia-mediated autophagy also clearly decreased the chemosensitivity of lymphoma cells treated with Dox (68).…”
Section: Hypoxia-induced Autophagy In Os Progressionmentioning
confidence: 99%
“…AEG-1 expression was analyzed in lymph node biopsies from 129 T-cell Non-Hodgkin lymphoma (T-NHL) patients and 17 control individuals revealing high AEG-1 expression in T-NHL patients with barely detectable levels in normal lymph nodes ( p < 0.01) [ 130 ]. AEG-1, LC3-II and Beclin-1 levels were found to be significantly higher in T-NHL tissues ( n = 30) versus normal lymph nodes ( n = 16) by Western blot, real-time PCR and IHC ( p < 0.001), suggesting a potential role of AEG-1 in regulating autophagy [ 131 ]. No other clinicopathological parameters were analyzed in these studies.…”
Section: Lymphoma and Leukemia And Aeg-1mentioning
confidence: 99%